Chemotherapy regimens for advanced pancreatic cancer: a systematic review and network meta-analysis - Gresham, Gillian K; Wells, George A; Gill, Sharlene; Cameron, Christopher; Jonker, Derek J (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Advanced pancreatic cancer confers poor prognosis and treatment advancement has been slow. Recent randomized clinical trials (RCTs) have demonstrated survival benefits for combination therapy compared to gemcitabine alone. However, the comparative benefits and harms of available combination chemotherapy treatments are not clear. We therefore conducted a systematic review and Bayesian network meta-analysis to assess the comparative safety and efficacy of chemotherapy regimens for the treatment of advanced pancreatic cancer. Methods MEDLINE, PubMed, EMBASE, Cochrane Central Registry of Clinical trials and abstracts from major scientific meetings were searched for RCTs published from 2002 to 2013. Key outcomes were overall survival (OS), progression free survival (PFS), and safety including grade 3–4 febrile neutropenia, neutropenia, vomiting, diarrhea, fatigue and sensory neuropathy. Bayesian network meta-analyses were conducted to calculate survival and safety outcomes using gemcitabine (GEM) as the reference comparator. Effect estimates and 95% credible intervals were calculated for each comparison. Mean ranks and the probability of being best were obtained for each treatment analyzed in the network meta-analysis. Results The search identified 23 studies involving 19 different treatment regimens and 9,989 patients. FOLFIRINOX, GEM/cisplatin/epirubicin/5FU (PEFG), GEM/NAB-paclitaxel (NAB-P), GEM/erlotinib+/-bevacizumab, GEM/capecitabine, and GEM/oxaliplatin were associated with statistically significant improvements in OS and PFS relative to gemcitabine alone and several other treatments. They were amongst the top ranked for survival outcomes amongst other treatments included. No significant differences were found for other combination chemotherapy treatments. Effect estimates from indirect comparisons matched closely to estimates derived from pairwise comparisons. Overall, combination therapies had greater risk for evaluated grade 3–4 toxicities over gemcitabine alone. Conclusions In the absence of head-to-head comparisons, we performed a mixed-treatment analysis to achieve high-quality information on the effectiveness and safety of each treatment. This study suggests that some combination therapies may offer greater benefits in the treatment of advanced pancreatic cancer than others. To more fully elucidate the comparative benefits and harms of different combination chemotherapy regimens, rigorously conducted comparative studies, or network meta-analysis of patient-level data are required.